Raman spectroscopy methods for detecting and imaging supported lipid bilayers. Issue 1 (2010) - Sweetenham Sweetenham, Claire S. Claire S.; Notingher Notingher, Ioan Ioan
Abstract : We have developed a Raman microspectroscopy system optimised for studying supported lipid bilayers (SLB). This system combines the benefits of Raman spectroscopy with the high spatial resolution of confocal microscopy. Furthermore, the additional incorporation of an atomic force microscope (AFM) makes it possible to directly correlate chemical information with spatial features of samples at the nanoscale. We focus on the limits of this system for detecting a single SLB and imaging its microdomains, and employ surface-enhanced Raman spectroscopy (SERS) to improve the sensitivity achieved with Raman microspectroscopy.